PENGARUH DEBT TO EQUITY RATIO, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA. - Ginting, Pebrianti; Munthe, Kornel (Jurnal Manajemen dan Bisnis, 2017)
The aim of this research is to analyze the influence of debt to equity ratio and earning per share the stock prices of manufacturing companies listed at the Indonesian Stock Exchange. The method of analysis used was linier multiple regression model. This research used secondary data, annual report of the manufacturing corporations during 2012-2014 with 120 unit of corporation as population and 30 unit taken sample by using purposive sampling method. The result of the research indicate that: debt to equity ratio have negative and not significant influence on the stock prices of the corporation, while earning per share have positive and signifikan influence on the stock prices of the corporation. Simultaneously debt to equity ratio and earning per share have signifikan influence on the stock prices of the corporation.